Desapego parental y el desarrollo emocional de niños con padres que ejercen la profesión docente en la esc. Luz Victoria Rivera de Mora, Balsas - El Oro, periodo lectivo 2017-2018 - Ramírez Maldonado, Lynnda Marcelle (2018)
Parental detachment causes serious emotional problems in children and young people, such as; the deep sadness, behavioral problems, problems of trust because the child does not feel protected by their parents, so the children look for a refuge, security and affection in third parties. It is relevant to mention that this research has a qualitative approach, because it is of a social nature, given that the area of knowledge is the education sciences and is configured as a humanistic study. This is also consistent with the lines of research established at the Universidad Nacional de Chimborazo, this line is: Humanities-Training of teaching staff and Learning Sciences and its design is non-experimental since the facts or the problem were observed in their real context so that the variables were not deliberately manipulated. The methods used in this research were: inductive-deductive method because after several questions corresponding to the research topic, it was possible to draw general conclusions based on particular facts; synthetic-analytical, since it is characteristic of the analysis of information and it serves to establish the theoretical foundation that is embodied in the methodological and hypothetical-deductive framework, because it allows to establish value judgments or anticipated responses to the investigative process. As conclusions, it was determined that the emotional development acquired by the child of parents who practice the teaching profession has characteristics such as; sadness, loneliness, anger, frustration, fear. The consequences of detachment are low school performance, problems of self-esteem and safety. It has also destroyed affective ties between parents and children.